Service Quality through Hotel Management Students Perception for Five Star Hotel Business in Khon Kaen Province - Pattanachak, Sivadon (Ratchaphruek Journal, 2021)
The purposes of this study were to (1) study the level of perceptions of service quality of the 5 star hotel in Khon Kaen province by hotel management students, (2) compare the perception level of service quality of a five star hotel with the personal factors of the students, and (3) analyse the relationship between perceptions of service quality and personal factors of the students. This study was a cross-sectional analytical research. The study used questionnaires with a 5-level rating scales were excellent, good, fair, poor and very poor. The content consists of 5 characteristics of service quality: tangibility, reliability, responsiveness, assurance and empathy. The questionnaire was verified content validity by three experts with the index of item objective congruence (IOC) was 0.91 and the reliability of Cronbach’s alpha was 0.96. The data were collected from the total population of 106 first-year students. The descriptive statistics used in the analysis were the frequency distribution, percentage, mean, standard deviation and the inferential statistics were independent t-test and chi-square test. The results of the research showed that the level of the perceptions of service quality in all aspects were at high level. The overall and the empathy perspective of service quality perception was significantly different with age (p-value <0.05). The relationship between the perceptions of service quality and age was statistically significant (p-value <0.05).